Study on the fracture propagation law of deep shale reservoir under the influence of different number of fracturing clusters - Zeng, Bo; Wu, Mingyang; Su, Yuliang; Guo, Yintong; Feng, Jiangrong; Gui, Junchuan; Lu, Jun (Frontiers in Energy Research, 2024)
Deep reservoirs have a large difference in geo-stress, and compared to shallow reservoirs, multiple clusters of fracturing are usually required to effectively improve the quality of reservoir reconstruction. In this paper, considering the relevant geological parameters of a certain reservoir in the southwest, multi-cluster reservoir fracturing models under three-dimensional conditions based on the cohesive element modelling method are established. Then, the quantitative rules of fluid pressure, fracture length, fracture aperture, fracture area, tensile failure rate, and the fractal dimension of fracture morphology under different fracturing cluster numbers were revealed. The results show that compared to conventional fracturing, multi-cluster fracturing can significantly increase the number of main fractures and improve the effectiveness of reservoir reconstruction.As the number of clusters increases, the number of main fractures in the reservoir increases, but it can also lead to the increase of small opening fractures, which may be unfavourable for the pumping of proppant and subsequent mining. Meanwhile, based on the fractal dimension results of fracture morphology, it was found that under this simulation condition, the number of fracturing clusters had a significant impact on the fractal dimension of fracturing fractures before the fracturing of six clusters, while after the fracturing of six clusters, the impact of the number of fracturing clusters on the fractal dimension of fracturing fractures decreased.Therefore, when considering factors such as the complexity of fractures, multi-cluster fracturing does not necessarily result in more fracturing clusters being better but should be comprehensively considered for optimization. This study has certain reference significance for selecting the spacing between multiple fracturing clusters.